Revolutionizing Equivalency Education: The Impact of EquivaLearn on Tutor Performance and Student Engagement - Muh Dliyaul Haq; Ria Indhirawati (Malaysia Journal of Invention and Innovation, 2023)
EquivaLearn is a comprehensive application developed to enhance the implementation of the equivalency education program in Sabah-Sarawak, Malaysia. This research article investigates the impact of EquivaLearn on tutor performance and student engagement in the program. The study employed a mixed methods approach, combining quantitative data from surveys and qualitative data from in-depth interviews with tutors and students. The findings revealed positive feedback and satisfaction with the application's accessibility, technical assistance, user interface, user experience, functionality, advantages, and efficiency. The survey results indicated that the majority of respondents agreed or strongly agreed with the effectiveness of EquivaLearn in various aspects. The application's features, such as attendance tracking, learning activity journals, resource downloads, and e-modules, were found to contribute to improved tutor monitoring, tutor management, access to learning resources, and overall program outcomes. The qualitative data provided valuable insights into the participants' experiences and perceptions, highlighting the convenience, support, and enhanced learning experience facilitated by EquivaLearn. The study concludes that EquivaLearn has a positive impact on tutor performance and student engagement in the equivalency education program, empowering tutors, students, and education administrators. Further feedback and analysis from a broader user base are recommended to refine the application and address any areas for improvement.